CAPITAL STRUCTURE AND INVESTMENT DECISION ON COMPANY VALUE ON THE INDONESIA STOCK EXCHANGE - Mesrawati Mesrawati; Amrita Sonia Kaur; Darshini Darshini; Mega Ningsih; David Beckham Manurung (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
Every company established aims to achieve maximum profit or maximum profit in the hope of increasing the value of the company. In order to increase the value of the company, the financial manager is expected to be able to manage company finances effectively and efficiently. Good corporate financial management can be seen from the value of the company. The value of a good company is reflected in its share price. Companies that have high stock prices, of course, high company values ​​as well as low stock prices reflect low company value. There are several factors that affect company value on capital structure, investment decision, profitability, and firm size. The purpose of this research is to find out and analyze capital structure and investment decision on company value on the Indonesia Stock Exchange. This study uses a quantitative research approach. This type of research is descriptive and quantitative. The nature of this research is cause and effect. The sample of this research is 100 financial statements of Property, Real Estate, and Building Construction Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The method of data analysis in this study used multiple linear regression analysis, which consisted of testing the hypothesis partially (t) and simultaneously (F). The results show that capital structure has a significant effect on company value. Investment decision has a unsignificant effect on company value. Profitability has a significant effect on company value. Firm size has a significant effect on company value. The results of simultaneously (F) show that capital structure, investment decision, profitability, and firm size have a significant effect on company value.